Government Policies and Private Housing Prices in Singapore - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 1997)
Regression models are used to show that interest rates, income growth rates and the supply of housing have not played a statistically significant role in the determination of private housing prices in Singapore between 1975 and 1994. Instead, private housing prices in Singapore were highly correlated with the prices for public-sector-built housing. Moreover, the timing of government policies relating to the use of compulsory savings for private housing finance purposes, the liberalisation of rules on public housing ownership criterion as well as for housing finance had a significant impact on private housing prices.